Multiple unbiased approaches identify oxidosqualene cyclase as the molecular target of a promising anti-leishmanial. Issue 5 (20th May 2021) - Paradela, Luciana S.; Wall, Richard J.; Carvalho, Sandra; Chemi, Giulia; Corpas-Lopez, Victoriano; Moynihan, Eoin; Bello, Davide; Patterson, Stephen; Güther, Maria Lucia S.; Fairlamb, Alan H.; Ferguson, Michael A.J.; Zuccotto, Fabio; et al.
Summary: Phenotypic screening identified a benzothiophene compound with activity against Leishmania donovani, the causative agent of visceral leishmaniasis. Using multiple orthogonal approaches, oxidosqualene cyclase (OSC), a key enzyme of sterol biosynthesis, was identified as the target of this racemic compound and its enantiomers. Whole genome sequencing and screening of a genome-wide overexpression library confirmed that OSC gene amplification is associated with resistance to compound 1 . Introduction of an ectopic copy of the OSC gene into wild-type cells reduced susceptibility to these compounds confirming the role of this enzyme in resistance. Biochemical analyses demonstrated the accumulation of the substrate of OSC and depletion of its product in compound ( S )-1 -treated-promastigotes and cell-free membrane preparations, respectively. Thermal proteome profiling confirmed that compound ( S )-1 binds directly to OSC. Finally, modeling and docking studies identified key interactions between compound ( S )-1 and the Ld OSC active site. Strategies to improve the potency for this promising anti-leishmanial are proposed. Graphical abstract: Highlights: Genetics and chemo-proteomics identify the target of a promising anti-leishmanial Biochemical assays confirm the direct inhibition of oxidosqualene cyclase in cells Docking and modeling studies identify key interactions between compound and target Strategies to improve the potency of this benzothiophene are proposed Abstract : Paradela et al. investigated the mechanism of action of a promising anti-leishmanial. Using genetics, chemo-proteomics, and biochemical approaches, the target of this benzothiophene was confirmed as oxidosqualene cyclase, a key enzyme of sterol biosynthesis. Docking and modeling identified key interactions between this compound and the active site of this enzyme.